Mapping bank securities across euro area sectors: Comparing funding and exposure networks - Anne-Caroline Hüser; Christoffer Kok Sørensen (European Central Bank (ECB), 2019)
We present new evidence on the structure of euro area securities markets using a multilayer network approach. Layers are broken down by key instruments and maturities as well as the secured nature of the transaction. This paper utilizes a unique dataset of banking sector crossholdings of securities to map these exposures among banks and economic and financial sectors. We can compare and contrast funding and exposure networks among banks themselves and of banks, non-banks and the wider economy. The analytical approach presented here is highly relevant for the design of appropriate prudential measures, since it supports the identification of counterparty risk, concentration risk and funding risk within the interbank network and the wider macro-financial network.
Keywords: D85; E44; G21; L14; 330; Interbank networks; macro-financial networks; multilayer networks; market microstructure; macroprudential analysis